Chitosan/β-TCP composites scaffolds coated with silk fibroin: a bone tissue engineering approach. (17th November 2021) - Piaia, Lya; Silva, Simone S; Gomes, Joana M; R Franco, Albina; Fernandes, Emanuel M; Lobo, Flávia C M; Rodrigues, Luísa C; Leonor, Isabel B; Fredel, Márcio C; Salmoria, Gean V; Hotza, Dachamir; Reis, Rui L
Abstract: Bone regeneration and natural repair are long-standing processes that can lead to uneven new tissue growth. By introducing scaffolds that can be autografts and/or allografts, tissue engineering provides new approaches to manage the major burdens involved in this process. Polymeric scaffolds allow the incorporation of bioactive agents that improve their biological and mechanical performance, making them suitable materials for bone regeneration solutions. The present work aimed to create chitosan/beta-tricalcium phosphate-based scaffolds coated with silk fibroin and evaluate their potential for bone tissue engineering. Results showed that the obtained scaffolds have porosities up to 86%, interconnectivity up to 96%, pore sizes in the range of 60–170 μm, and a stiffness ranging from 1 to 2 MPa. Furthermore, when cultured with MC3T3 cells, the scaffolds were able to form apatite crystals after 21 d; and they were able to support cell growth and proliferation up to 14 d of culture. Besides, cellular proliferation was higher on the scaffolds coated with silk. These outcomes further demonstrate that the developed structures are suitable candidates to enhance bone tissue engineering.